ANALYSIS OF THEMATIC PROGRESSION IN ENGLISH OF ECONOMIC ARTICLES OF BATAMNEWS.COM - Fitriana, Nur; Nugraha, Hendra; Putra, Hilarius R. P. (Universitas Negeri Gorontalo, 2024)
This study analyzes thematic progression patterns in English economic articles on Batamnews.com to understand how economic information is structured and conveyed in digital journalism. Using Halliday and Hasan's functional approach, which categorizes themes into topical, interpersonal, and textual groups, this qualitative research examines five selected articles, focusing on their introductions to identify thematic progression patterns such as reiteration, zigzag, and multiple themes. The analysis reveals that reiteration patterns dominate, followed by zigzag patterns and multiple theme patterns. These findings highlight the significant role of these patterns in enhancing textual coherence and reader engagement. This study provides new insights into the writing strategies of digital economic journalism and contributes to linguistic research as well as economic journalism practices, particularly in the context of Batamnews.com as an influential digital platform in the Batam region.